As almas do gentio da terra: a escravidão indígena em São Paulo na instituição do sistema da Administração - Ramos, Antonio Martins (2021)
The object of this research is the form of indigenous slavery as it was practiced in colonial São Paulo, during the process of establishing the social and legal system called Administração. The legal prohibition of slavery, its ethical, moral and religious limits, did not prevent the exploitation of labor, captivity and the possession of individuals. This legal condition of indigenous freedom created a specific and contradictory social situation for the Indians and unsatisfactory for colonists and missionaries. The legal uncertainties of indigenous exploitation put pressure on local governments and city councils, so that throughout the 17th century, conflicts intensified, leading the Portuguese crown to establish the legal institution of the Administração, based on traditional and daily practices. These were based on the model of aldeamentos as centers of establishment and requisition of Indians, and in the specific case of São Paulo, due to the intensity and frequency of boarding expeditions that went beyond the rules of the resgates, attacking the Jesuit missions. The violence committed against the Indians was considered abuses, but their restraint by the authorities never occurred effectively. The Indians were left with resistance, submission, or adaptation. However, they did not act passively, even in situations of silencing and genocide. Through the preservation of cultures, the relationship between ancestral cosmogony and Catholic Christianity in processes of adaptive resistance, they found ways to insert themselves in colonial society, although always in the condition of subordinates. Due to the nature of this everyday reality and the evidence in historical sources, we believe that the Administração system practiced in São Paulo served as a cover for the legal freedom of the Indians, and constituted a consolidated and effective model of slavery